Excited Delirium and Sudden Death: A Syndromal Disorder at the Extreme End of the Neuropsychiatric Continuum - Mash, Deborah C. (Frontiers in Physiology, 2016)
Over the past decade, the excited delirium syndrome (ExDS) has raised continued controversy regarding the cause and manner of death of some highly agitated persons held in police custody, restrained or incapacitated by electrical devices. At autopsy, medical examiners have difficulty in identifying an anatomic cause of death, but frequently cite psychostimulant intoxication as a contributing factor. The characteristic symptoms of ExDS include bizarre and aggressive behavior, shouting, paranoia, panic, violence toward others, unexpected physical strength, and hyperthermia. Throughout the United States and Canada, these cases are most frequently associated with cocaine, methamphetamine, and designer cathinone abuse. Acute exhaustive mania and sudden death presents with behavioral symptoms that are identical to what is described for ExDS in psychostimulant abusers. Bell's mania or acute exhaustive mania was first described in the 1850's by American psychiatrist Luther Bell in institutionalized psychiatric patients. This rare disorder of violent mania, elevated body temperature and autonomic collapse continued to be described by others in the psychiatric literature, but with different names until the first cases of ExDS were seen at the beginning of the cocaine epidemic by medical examiners. The neurochemical pathology examination of brain tissues after death revealed a loss of dopamine transporter regulation together with increases in heat shock protein 70 (hsp70) expression as a biomarker of hyperthermia. The similarity in the behavioral symptoms between extremely agitated psychostimulant abusers and unmedicated psychiatric patients suggests that a genetic disorder that leads to dysregulated central dopamine transporter function could be a precipitating cause of the acute delirium and sudden death. While the precise cause and mechanism of lethality remains controversial, the likely whys and wherefores of sudden death of ExDS victims are seen to be “biological,” since excessive dopamine in the brain triggers the manic excitement and delirium, which unabated, culminates in a loss of autonomic function that progresses to cardiorespiratory collapse.